Research progress on short-term prognosis of acute-on-chronic liver failure. (2nd January 2023) - Ma, Luyao; Liu, Siqi; Xing, Hao; Jin, Zhenjing
ABSTRACT: Introduction: Acute-on-chronic liver failure (ACLF) is a clinical syndrome characterized as a severe condition with rapid progression, poor therapeutic response and poor prognosis. Early and timely evaluation of the prognosis is helpful for providing appropriate clinical intervention and prolonging patient survival. Areas covered: Currently, there are no specific dynamic and comprehensive approaches to assess the prognosis of patients with ACLF. This article reviews the progress in evaluating the short-term prognosis of ACLF to provide future directions for more dynamic prospective large-scale multicenter studies and a basis for individualized and precise treatment for ACLF patients. We searched PubMed and Web of Science with the term 'acute on chronic liver failure' and 'prognosis.' There was no date or language restriction, and our final search was on 26 October 2022. Expert opinion: ACLF is a dynamic process, and the best prognostic marker is the clinical evolution of organ failure over time. New prognostic markers are developing not only in the fields of genetics and histology but also toward diversification combined with imaging. Determining which patients will benefit from continued advanced life support is a formidable challenge, and accurate short-term prognostic assessments of ACLF are a good approach to addressing this issue.